Biomonitoring of heavy metals in the feathers raptors from eastern Anatolia of Türkiye - Özdemir, Özgür; Azizoğlu, Erkan (Frontiers in Ecology and Evolution, 2025)
This study aimed to determine the levels of heavy metal(loid) in the primary, secondary and breast feathers of carcasses of raptor species detected on highways within the borders of Van and Hakkari Provinces. The study was planned to take place between 1 April 2021 and 30 May 2022, including the spring and autumn migration periods. The study stations were selected considering the routes where birds breed and are frequently active. In addition, observations were made along the way, and the amounts of As, Cd, Cr, Cu, Ni, Pb, and Zn in the primary and secondary wing feathers and breast feathers of 19 carcasses belonging to 11 species collected from 3 families (Accipitridae, Falconidae, Strigidae) belonging to two raptor orders (Accipitriformes, Strigiformes) were analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES). The metal(loid) with the highest accumulation rates in the carcass feathers were ranked as follows: Zn > Cu > Cr > Ni > Pb > As > Cd. Cd values were not found in the Strigidae and Falconidae families. It was only read in the family Accipitridae. There is a significant difference in the average Cu metal level between the Falconidae and Accipitridae families. When As, Ni, Cr and Pb evaluated, no difference was seen between the species groups (p>0.05). There was a difference between Zn and Cd, but no difference was observed for the other elements (p<0.05). According to the detected concentrations of these metals, it was seen that the levels of accumulation in the feathers of the examined birds varied depending on their feeding habits.